PENGARUH PERSEPSI HARGA DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN MENGGUNAKAN PRODUK KOSMETIK (STUDI PADA SWALAYAN GRAND HERO DI KOTA PALU) - ADAWIAH, RABIATUL (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2015)
The purpose of this study is to determine the influence of price and brand image both simultaneously and partially to customer loyalty at grand hero Supermarkets in the city of Palu. The independent variables used in this study are price and brand image. While the dependent variable is Customer Loyalty (Y). The research method used in this research is descriptive causal method. The sample used in this study were as many as 93 respondents with the form of sampling using accidental sampling and Purposive Sampling techniques. Data analysis method used in this research is multiple linear regression analysis method. The results of this study indicate that simultaneously the price and brand image have a significant effect on customer loyalty at grand hero supermarket in the city of hammer. Partially significant effect on customer loyalty using viva cosmetic product at grand hero supermarket in Palu City.